ACUTE AEROBIC EXERCISE-INDUCED DECREASE IN BLOOD PRESSURE IS ASSOCIATED WITH CHRONIC BLOOD PRESSURE CHANGES IN PATIENTS WITH RESISTANT HYPERTENSION. (June 2022) - Lopes, Susana; Mesquita-Bastos, José; Garcia, Catarina; Oliveira, José; Polónia, Jorge; Alves, Alberto; Ribeiro, Fernando
Abstract : Objective: The acute blood pressure (BP) decrease after an exercise training session seems to correlate with the chronic BP reductions following exercise training programs in participants with pre-hypertension; yet, among patients with resistant hypertension (RH) it is unknown. This study aims to investigate the association between the magnitude of BP decrease after acute exercise and the change in 24-hr ambulatory blood pressure (ABP) after an aerobic exercise intervention in patients with RH. Design and method: EnRicH trial was a randomized clinical trial assessing the effects of a 12-week moderate-intensity aerobic exercise program in participants with RH. In the present study, twenty-six patients (mean age 59.3 ± 8.2 years, 58.3% male) with RH that participated in the intervention arm of the EnRicH trial were included. Office and ABP measurements were obtained before and after the 12-week aerobic exercise training program. To assess the acute effect, resting BP measures were assessed before and 10 minutes after each exercise session of the third week of the exercise program. Exercise sessions were supervised, occurred three times per week, and included 40 min of aerobic exercise at 50% to 70% of VO2max and a 10-minute cooldown. Results: Resting systolic (-9.4 ± 7.0, p < 0.001) and diastolic BP (-1.9 ± 3.4, p = 0.10) were significantly reduced after acute exercise. 24hr systolic (-6.2 ± 12.1, p = 0.015) and diastolic BP (-4.42 ± 6.1, p = 0.001) an office systolic (-10.9 ± 15.2, p = 0.001) and diastolic BP (-5.9 ± 11.1, p = 0.013) were significantly decreased after the exercise program. The acute changes were correlated with the chronic decrease in 24hr ambulatory systolic (r = 0.556, p = 0.003) and diastolic (r = 0.484, p = 0.012) BP, and office systolic (r = 0.478, p = 0.014) and diastolic BP (r = 0.452, p = 0.020). Multiple regression analysis revealed that the acute effect of exercise was an independent predictor of the chronic effect on systolic BP (ß = 0.556, adjusted r2 = 0.280, p = 0.003) BP. Conclusions: The magnitude of the acute effect of exercise in BP correlates with the chronic decrease in both office and 24hr BP effects. These results suggest that it is possible to predict those patients that are less likely to improve BP with an exercise training program without the burden of a period of several months of intervention.